Renewal of Thinking about International Economic Integration - Vu Kim Diem, Do Thi Ngoc Quy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
International integration is an inevitable and objective trend, strongly attracting the participation of all countries and regions in the world. With its vastness and complexity, international integration has had a strong impact on all nationalities, all fields of social life, especially for the economy. For Vietnam, international integration has brought opportunities and opportunities, and at the same time also created real challenges and risks in economic development. Therefore, the urgent issue now is to fully and deeply identify and have reasonable strategies, take advantage of opportunities, overcome risks in order to develop economic in integration and development has important theoretical and practical implications.